Relationship between Diabetes mellitus and Urinary tract infections (Baghdad Science Journal, 2008)
Blood and urine samples were collected from 203 patients to study the relationship between Diabetes mellitus and urinary tract infections (UTI). Blood and urine specimens were subjected for estimation of random blood sugar, in addition to detection of the most pathogen bacteria which cause urinary tract infection in diabetic patients.The study included the detection of bacterial sensitivity to some antibiotics used in treating urinary tract infections, and also included the study of genetic basis which cause both types of diabetes mellitus.The results can be summarized as follows: The incidence of type ? diabetes in males was (35.8%), and (45.9%) in females . and type 2 diabetes in males was (49.6%), while in females was (40.16%).The incidence of urinary tract infection in females was higher (69.6%) in comparison to males (37%).Escherichia coli was the most causative agent of urinary tract infections in diabetic males (19.7%), while Candida albicans was the most causative agent in urinary tract infections in females (18.8%).The majority of isolated bacteria were highly resistant to Gentamycin, Tetracycline, Ampicillin, Penicillin G, while they were sensitive to Cephotaxim, Cephalexin, Ciprofloxacin.